Legal Study of Airport Pass Supervision At the Regional Airport Authority Office II: Kajian Hukum Pengawasan Pas Bandar Udara Di Kantor Otoritas Bandar Udara Wilayah II - Silvianda (UPMI Proceeding Series, 2023)
The objective of this article is to give a study or review regarding a procedure for an oversight of Airport Pass for those people entering Security Restricted Area at working area of Civil Aviation Authority Region II, which henceforth called CAA. One of the methods in entering Security Restricted Area is Airport Pass for people, which henceforth called Airport Pass, which is defined with a procedure. The procedures at least contain the application for: publishing, renewal, recurrent, evaluation, type and area, quota, security awareness, design, renewal design, obligation, penalty, and the one that will be studied further in this article which is a procedure of an oversight for Airport Pass. The purpose of this procedure is establishment of a standard oversight system in security restricted area for each airport in CAA’s working region. Least but not last this article is encouraging an establishment of a standard operating procedure related to an oversight of airport pass which has not been regulated on existing CAA’s standard operating procedure.